Implementasi MDLC dan Pose to Pose dalam Film Animasi 3D Sejarah Kerajaan Melayu Siak - Wenda Novayani; Galih Eka Budiansyah (Politeknik Negeri Batam, 2022)
The lack of engaging historical learning media is one of the causes of the lack of interest in learning history for the younger generation. This study aims to create a learning media packaged in a 3D animated film about the history of the Siak kingdom in Riau province. The story's content in the animated movie did take from the book History of the Siak Kingdom written by the Siak Malay Kingdom History Writing Team, published by the Riau Malay Cultural Heritage Institute, published in June 2011. Using the Multimedia Development Life Cycle (MDLC) method, developing the film consists of six stages: concept, design, material collection, assembly, testing, and distribution. Meanwhile, to make the impression of smooth and realistic animation movement using the pose-to-pose method. The test relies on two experts as validators, namely animation media experts and film experts. The results showed that the MDLC stages helped make animated films better and more structured. The study results resulted in a 3D animated film of the Kingdom of Siak, which has smooth and realistic animation movements and has met the requirements of filmmaking and is worthy as a medium of information for learning history.